The Role of Signal Transducer and Activator of Transcription 3 (STAT3) and Its Targeted Inhibition in Hematological Malignancies - Arora, Loukik (Cancers (Basel), 2018)
Signal transducer and activator of transcription 3 (STAT3), a member of the STAT protein family, can be phosphorylated by receptor-associated Janus kinases (JAKs) in response to stimulation by cytokines and growth factors. It forms homo- or heterodimers that can translocate to the cell nucleus where they act as transcription activators. Constitutive activation of STAT3 has been found to be associated with initiation and progression of various cancers. It can exert proliferative as well as anti-apoptotic effects. This review focuses on the role of STAT3 in pathogenesis i.e., proliferation, differentiation, migration, and apoptosis of hematological malignancies viz. leukemia, lymphoma and myeloma, and briefly highlights the potential therapeutic approaches developed against STAT3 activation pathway.